Exosomal miR-126 as a circulating biomarker in non-small-cell lung cancer regulating cancer progression. Issue 1 (December 2017) - Grimolizzi, Franco; Monaco, Federica; Leoni, Francesca; Bracci, Massimo; Staffolani, Sara; Bersaglieri, Cristiana; Gaetani, Simona; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Saccucci, Franca; Neuzil, Jiri; et al.
Abstract Lung cancer is one of the leading causes of cancer-related deaths. It is diagnosed mostly at the locally advanced or metastatic stage. Recently, micro RNAs (miRs) and their distribution in circulation have been implicated in physiological and pathological processes. In this study, miR-126 was evaluated in serum, exosome and exosome-free serum fractions in non-small cell lung cancer (NSCLC) patients at early and advanced stages, and compared with healthy controls. Down-regulation of miR-126 was found in serum of advanced stage NSCLC patients. In healthy controls, circulating miR-126 was equally distributed between exosomes and exosome-free serum fractions. Conversely, in both early and advanced stage NSCLC patients, miR-126 was mainly present in exosomes. Different fractions of miR-126 in circulation may reflect different conditions during tumour formation. Incubation of exosomes from early and advanced NSCLC patients induced blood vessel formation and malignant transformation in human bronchial epithelial cells. On the other hand, exosome-enriched miR-126 from normal endothelial cells inhibited cell growth and induces loss of malignancy of NSCLC cells. These findings suggest a role of exo-miRs in the modulation of the NSCLC microenvironmental niche. Exosome-delivered miRs thus hold a substantial promise as a diagnostics biomarker as well as a personalized therapeutic modality.